2019
DOI: 10.1038/s41598-018-38057-6
|View full text |Cite
|
Sign up to set email alerts
|

micro-RNAs dependent regulation of DNMT and HIF1α gene expression in thrombotic disorders

Abstract: MicroRNAs (miRNAs) are involved in a wide variety of cellular processes and post-transcriptionally regulate several mechanism and diseases. However, contribution of miRNAs functioning during hypoxia and DNA methylation together is less understood. The current study was aimed to find a shared miRNAs signature upstream to hypoxia (via HIF gene family members) and methylation (via DNMT gene family members). This was followed by the global validation of the hypoxia related miRNA signature using miRNA microarray me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…NETs are cytotoxic and procoagulant, in part due to the release of DNA-histone complexes and double-stranded DNA, histones, and HMGB1 [ 41 , 42 ]. It is understood that the increase in DNA-binding proteins, extracellular ribosomal RNA, and micro-RNAs, may be related to thrombosis [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…NETs are cytotoxic and procoagulant, in part due to the release of DNA-histone complexes and double-stranded DNA, histones, and HMGB1 [ 41 , 42 ]. It is understood that the increase in DNA-binding proteins, extracellular ribosomal RNA, and micro-RNAs, may be related to thrombosis [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…c-Myc is upregulated in prostate cancer cells and inhibits miR-23a and miR-23b at the transcriptional level, resulting in its target protein mitochondrial glutaminase overexpression [ 35 ]. Using miRNA microarray meta-analysis, it was found that miR-23b was associated with hypoxia-related pathways mediated by the HIF gene family, which revealed the important role of miR-23b in hypoxia and thrombosis pathway [ 36 ]. E2F1 binding sequence participates in the expression of C9orf3 transcripts of host genes in miR-23b/27b/24 clusters, thus promoting cell migration [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We searched for studies published in EMBASE, Medline, PubMed, Web of Science, and the Cochrane Clinical Trials Database between January 2000 and October 2021, using the keywords: (1) rivaroxaban; (2) warfarin; (3) venous thromboembolism; and (4) bleeding. Combinations of keywords using the Boolean operators "and/or" were adopted for the search strategy.…”
Section: Study Selectionmentioning
confidence: 99%